MENGAJARKAN NILAI-NILAI KARAKTER TENTANG PERSAHABATAN SEBAYA KEPADA ANAK USIA 12-14 TAHUN DENGAN MENGGUNAKAN KOMIK STRIP - zahiyah, haura; Hadi Prayitno, Eko (Qualia: Jurnal Ilmiah Edukasi Seni Rupa dan Budaya Visual, 2023)
This study aims to understand the social environment around children that can affect personality at the age of 12-14 years through the moral messages contained in the creation of comic strips. Introducing the value of character education in daily life through comics using digital drawing techniques. The work made into reading books is in the form of comic strips where there are stories packaged according to educational points that are easily understood and carried out by children aged 12-14 years. This comic consists of a three-strip panel model created with illustrative visualization using the artist's personal style. Using a qualitative method with a Research-led practice approach by collecting data first before the practice of creating works of art is carried out. Through the collection of observational data types, literature studies (preliminary study), interviews with expert sources (results of internships), and the results of exploration of works. Until the final results of the creation of works are implemented to the community, together with the collection of user opinion data (interviews). The work from this research has an output in the form of a comic book which is designed as an alternative media to support character education learning that can be utilized both inside and outside of school.